Health capital and the prenatal environment: The effect of maternal fasting during pregnancy - Douglas Almond; Bhashkar Mazumder (Federal Reserve Bank of Chicago, 2009)
We use the Islamic holy month of Ramadan as a natural experiment in fasting and fetal health. In Michigan births 1989-2006, we and prenatal exposure to Ramadan among Arab mothers results in lower birthweight and reduced gestation length. Exposure to Ramadan in the first month of gestation is also associated with a sizable reduction in the number of male births. In Census data for Uganda, Iraq, and the US we find strong associations between in utero exposure to Ramadan and the likelihood of being disabled as an adult. Effects are particularly large for mental (or learning) disabilities. We also find significant effects on proxies for wealth, the sex composition of the adult population, and more suggestive evidence of effects on schooling and earnings. We find no evidence that negative selection in conceptions during Ramadan accounts for our findings, suggesting that avoiding Ramadan exposure during pregnancy is costly or the long-term effects of fasting unknown.
Keywords: 330; Schwangerschaft; Ernährung; Religion; Islam; Kinder; Gesundheit; Kognition; Welt